LEGAL FRAMEWORK ON GREEN BUILDING IN INDONESIA AND THE ALTERNATIVE POLICY - Wuri Virgayanti (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2017)
As buildings are one of the highest energy consumers from all over the world, there is special need to focus on how to mitigate energy consumption through regulation and policy. Responding this necessity, the concept of green building is being implemented in many countries along with Indonesia as an alternate to the traditional building concept. However there is slow movement in implementing this concept, especially in Indonesia. From legal viewpoint this paper will aim to answer why the Indonesian green building sector is not well developed. The method used in this paper is normative legal research. The analysis finds that the slow movement is due to the lack of the regulatory framework on its subject. Moreover, there is only little support from the government toward policies that might drive growth of the green building development. In light of this, there should be robust and strong regulatio. This can be achieved at the national level by regulating green buildings and also having government policies that encourage the development of green buildings.